Enhanced heat transfer in tubes based on vascular heat exchangers in fish: Experimental investigation. (July 2019) - Navickaitė, Kristina; Mocerino, Andrea; Cattani, Luca; Bozzoli, Fabio; Bahl, Christian; Liltrop, Klaus; Zhang, Xiaodan; Engelbrecht, Kurt
Graphical abstract: Highlights: Heat exchanger emulated from a vascular counter-flow heat exchanger geometry found in fishes. Experimental results demonstrate increase in Nusselt number up to 500% in a counter-flow heat exchanger. The global thermo-hydraulic performance increase up to 160% at constant pumping power. Selective laser melting technology was used to manufacture investigated double corrugated tubes. Abstract: A double corrugated tube geometry for improved heat transfer performance inspired by vascular heat exchangers found in fish such as the tuna and the opah is presented. The geometry features a cross section that varies continuously in the flow direction while maintaining a constant hydraulic diameter, which gives enhanced heat transfer at a relatively low increase in pressure drop. Five ellipse-based tubes with varying corrugation severity and period that emulate blood vessels of fish were produced in an aluminium alloy using additive manufacturing technology. Thermal performance of the novel tube design was experimentally investigated in a counter flow tube-in-shell heat exchanger in a range of Reynolds numbers from 1000 to 2500. Correlations for the Nusselt number and friction factor for each tube are proposed and the experimental results show that the Nusselt number increases up to 500% in corrugated tubes compared to a straight tube. The global thermo-hydraulic performance, evaluated for the same pumping power, of the double corrugated tubes is up to 160% higher than that of a straight tube.